The Design of a Leakage Detection System for Industrial and Mining Wastewater Pipelines Based on Multi-Electrode Method Integration - Zhang Xuanning; Nai Changxin; Liu Jingcai; Li Chenglong; Zhang Jie (E3S Web of Conferences)
To address the issue of industrial and mining wastewater leakage, this paper proposes a novel detection method for underground non-pressurized pipelines based on the combination of multiple electrical methods. The method integrates the high-density electrical method and the natural potential method, utilizing the naturally powered natural potential method for real-time monitoring. When a suspected leakage is de- tected, the high-density electrical method is used for precise localization and analysis of the leakage, enabling effective monitoring of industrial and mining wastewater leakage. A corresponding portable detection system has been designed, and both the detection method and the system have been validated through experiments.